Tendencia del marketing de influencers en la publicidad de instagram de la marca Lipofit - Vinces Troya, José Alfredo (2021)
This case study was carried out with the aim of analyzing the different digital marketing strategies and the use of influencers as tools to spread the Lipofit brand advertising on the Instagram social network. The techniques used were by observing the profiles of five young Ecuadorian influencers who in the different Instagram formats published advertising content of the product for several months in 2021, the interview technique was also carried out directly and virtually with two professionals; one expert in multimedia and brand management, in order to reinforce the development of research and, on the other hand, the contribution of the opinions of a Community manager focused on the management of social networks. Digital marketing is currently linked mainly to commercial dynamics and plays a fundamental role because it builds an interactive space with the user that will have at their disposal products that suit their needs. Lipofit is a natural product in the form of pills that helps to lose weight, acts by eliminating the accumulation of fat in the body, burns calories and is promoted in Ecuador by young women who have been on television or who continue, for being known at the level The most effective national strategy is to reach a large number of potential consumers.